Thermal properties of injection moulded polylactic acid 13 kenaf fibre biocomposite - Anuar, Hazleen; Ahmad, Zuraida (Plastics and Rubber Institute Malaysia, 2011)
Biocomposite made of polylactic acid (PLA) reinforced with natural kenaf bast fibre (KF) using twin screw extruder and injection molding machine has been developed. The effect of kenaf fibre content on crystallization and melting behavior has been studied by means of differential scanning calorimetry (DSC). The amourphous state of PLA was remain unchanged with kenaf fibre content. Although there were increment in melting enthalpy (94Hm) and cold-crystallization enthalpy (94Hcc), but it was not significant to cause kenaf fibre to act as nucleating agent for PLA. The effect of kenaf fibre content on the stiffness of the PLA-KF biocomposite at elevated temperature has been investigated by using dynamic mechanical analyzer (DMA). The storage modulus (E 19) of the composites is higher as compared to unreinforced PLA, whereas the mechanical loss factor (tan d) decreases with kenaf fibre content which can be associated to the compatibility of PLA matrix and kenaf fibre.